2008
DOI: 10.1364/ao.47.002227
|View full text |Cite
|
Sign up to set email alerts
|

Temperature measurements of turbid aqueous solutions using near-infrared spectroscopy

Abstract: We report a method that uses near-infrared spectroscopy and multivariate analysis to measure the temperature of turbid aqueous solutions. The measurement principle is based on the fact that the peak wavelength of the water absorption band, with its center near 1440 nm, shifts with changes in temperature. This principle was used to measure the temperatures of 1 mm thick samples of aqueous solutions containing Intralipid (2%), which are often used as optical phantoms for biological tissues due to similar scatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…1 Other applications include the estimation of temperature from the change in optical, property measured. Temperature can be estimated from changes in the absorbance 2 however, in turbid media, variation in scatter introduces an uncertainty in the path length, making it difficult to reliably estimate temperature from optical extinction coefficients. Uncoupling the effect of scattering on absorption may reduce this obscurity, offering the potential for accurate measurements of temperature in turbid solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Other applications include the estimation of temperature from the change in optical, property measured. Temperature can be estimated from changes in the absorbance 2 however, in turbid media, variation in scatter introduces an uncertainty in the path length, making it difficult to reliably estimate temperature from optical extinction coefficients. Uncoupling the effect of scattering on absorption may reduce this obscurity, offering the potential for accurate measurements of temperature in turbid solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature-induced changes in the optical properties of Intralipid have been described previously. Kakuta et al 2 reported the temperature dependence of absorbance at 1440 nm using a spectrophotometer and proposed a method to measure the temperature of turbid aqueous solutions, but they did not recover the absorption coefficient. McGlone et al 5 determined the temperature dependence of absorption and reduced scattering coefficients of Intralipid using continuous wave photon migration measurements from 700 to 1000 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have been studying a convenient non-contact way of using near-infrared spectroscopy (NIRS) for measuring the temperature of aqueous solutions [21][22][23]. This method is based on the temperature dependence of the near-infrared (NIR) absorption of water.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature dependence has been known in NIR spectrometry in biomedical, agricultural, and polymer sciences, but it has usually been regarded as a disturbance. While some experimenters have made use of it to measure the temperature of various samples that contain water [23,25,[28][29][30], others have tried to cancel out the temperature effect in noninvasive measurements of glucose concentration in vivo [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…microscopic scale was demonstrated recently [2], [3]. This technique uses the spectroscopic measurement of the near-IR stretching band of water [4], which changes both its absorption amplitude and shape as a function of temperature.…”
mentioning
confidence: 99%